Austria : Publication of Financial Sector Assessment Program Documentation-Technical Note on Banking Oversight. (IMF Staff Country Reports; Country Report ;, 2020)
This paper on Austria includes a targeted review of banking regulation and supervision, with a focus on topics related to the supervision of less significant institutions. The national transposition and implementation of EU directives and regulations has significantly closed some of the gaps identified in 2013. Oversight of bank loan portfolios was strengthened by guidance from the European Central Bank and European Banking Authority (EBA) concerning nonperforming loans and forborne exposures, and by EU regulation. As noted in the previous Basel Core Principles assessment, the Austrian Banking Act (BWG) and regulations do not establish an adequate framework for monitoring and addressing transactions with related parties; and the BWG does not require ex-ante approval for acquiring qualifying holdings in undertakings outside the financial sector. Although the BWG amendments strengthened the duties and responsibilities of credit institutions' supervisory boards, operationally the role may be made more robust by increasing interaction between the supervisory board and banking supervisors.